Altered Corticomuscular Coherence (CMCoh) Pattern in the Upper Limb During Finger Movements After Stroke - Guo, Ziqi; Qian, Qiuyang; Wong, Kiufung; Zhu, Hanlin; Huang, Yanhuan; Hu, Xiaoling; Zheng, Yongping (Frontiers in Neurology, 2020)
Background: Proximal compensation to the distal movements is commonly observed in the upper extremity (UE) in patients with chronic stroke. However, the cortical origin of this compensation has not been well understood. In this study, corticomuscular coherence (CMCoh) and electromyography (EMG) analysis were adopted to investigate corticomuscular coordinating mechanism of post-stroke compensatory activities of proximal UE in distal motions of the affected hands. Method: Fourteen chronic stroke subjects and ten age-matched unimpaired controls conducted isometric finger extensions and flexions at 20% and 40% of maximal voluntary contractions. Electroencephalography (EEG) data were recorded from the sensorimotor area and EMG signals were captured from extensor digitorum (ED), flexor digitorum (FD), triceps brachii (TRI), and biceps brachii (BIC) to investigate the CMCoh peak values in the Beta band. EMG parameters (i.e. the EMG activation level and co-contraction index) were analyzed to evaluate the compensatory muscular patterns in the upper limb. Result: The peak CMCoh with statistical significance (𝑃<0.05) was found shifted from the contralateral side to the ipsilateral side in the proximal UE muscles; while to the central regions in the distal UE muscle in chronic strokes. Significant differences (P<0.05) were observed in both peak ED and FD CMCohs during finger extensions between the two groups. The unimpaired controls exhibited significant intragroup differences between 20% and 40% levels in extensions for peak ED and FD CMCohs (P<0.05). The stroke subjects showed significance differences in peak TRI and BIC CMCohs (P<0.01). No significant inter- or intra-group difference was observed in peak CMCoh during finger flexions. EMG parameters showed higher EMG activation levels in TRI and BIC muscles (P<0.05), and higher CI values in the muscle pairs involving TRI and BIC during all the extension and flexion tasks in the stroke group than those in the control group (P<0.05). Conclusion: The post-stroke proximal muscular compensations from the elbow to the finger movements were cortically originated, with the center mainly located in the contralesional hemisphere.